Deep Learning Classification Method to Detect and Diagnose the Cancer Regions in Oral MRI Images (Medico Legal Update, 2021)
The paper proposes deep learning algorithm used to classify the oral images into either normal or abnormalimages. The cancer regions are segmented using morphological operations. The segmented cancer regionsare further diagnosed into ‘Mild’ or ‘Severe’ using deep learning algorithm. The main advantage of the deeplearning algorithm is that it requires minimum number of oral images for both classification and diagnosisstages of the proposed work. In this paper, the total number of cancers affected oral images used is about160 and the proposed oral cancer detection system using CNN classification approach classifies 159 canceraffected oral images correctly and achieves 99.3% of detection rate.